Examining the Effect of Ineffective Parenting and Low Self-Control on Athletes’ PED Use - Kabiri, Saeed (International criminal justice review, 2020)
The prevalence of performance-enhancing drug (PED) use at different levels of professional sport has become an important social issue, particularly when considering recent high-profile incidents from professional sports and the Olympics. Due to the myriad of individual, team, and sociopolitical consequences that can stem from PED use, it becomes critical to study the etiology of PED involvement among athletes regarding this deviant behavior. Gottfredson and Hirschi’s general theory of crime is one such theory that may aid in explaining this phenomenon. As such, the main purpose of this study was to investigate the relationships between effective parenting, self-control, and athletes’ use of banned PEDs. Survey data from 784 professional athletes in Iran were collected, and the findings indicated that ineffective parenting, low self-control capacity, and self-control desire had significant effects on PED use. In addition, moderation effects and gender analyses were examined. Specific findings, policy implications, and study limitations are discussed.